2009
DOI: 10.1007/s12549-009-0013-5
|View full text |Cite
|
Sign up to set email alerts
|

Fossil insects from the Late Oligocene Enspel Lagerstätte and their palaeobiogeographic and palaeoclimatic significance

Abstract: Fossil insects can provide unique insights into evolutionary history, and their study has become increasingly important in recent decades. In this paper, we give an overview of the insect taphocoenosis from the upper Oligocene Enspel Lagerstätte (Germany) and discuss taphonomic similarities with other localities. Among the fossil insects identified, terrestrial groups are highly dominant, with march flies (Bibionidae) and weevils (Curculionoidea) being the most common groups; aquatic insects are rare. We provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…As reported from other maar‐type lagerstätten (Lutz ; Wedmann et al . ), arthropods with fully or semi‐aquatic lifestyle are rare in such taphocoenoses: at Foulden Maar, they include a stone fly, a trichopteran larval case, as yet unidentified insect larvae and possibly aquatic hydrophylid beetles. The arthropod fauna is clearly dominated by adults of non‐aquatic, mainly ground‐dwelling taxa of forest floor, leaf litter and wood habitats such as bark bugs, weevils, scale insects, termites and ants.…”
Section: Discussionmentioning
confidence: 99%
“…As reported from other maar‐type lagerstätten (Lutz ; Wedmann et al . ), arthropods with fully or semi‐aquatic lifestyle are rare in such taphocoenoses: at Foulden Maar, they include a stone fly, a trichopteran larval case, as yet unidentified insect larvae and possibly aquatic hydrophylid beetles. The arthropod fauna is clearly dominated by adults of non‐aquatic, mainly ground‐dwelling taxa of forest floor, leaf litter and wood habitats such as bark bugs, weevils, scale insects, termites and ants.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose to attribute these fossils to Oligaeschna, in accordance with Wedmann (2000: fig. 5) and Wedmann et al (2010: fig. 6d) who indicated that it is 'probably Oligaeschna jungi'.…”
Section: )mentioning
confidence: 96%
“…The Odonata are relatively rare, represented by a total of about 70 fossils, roughly 0.6 per cent of all insect finds. Of those, 12 fossils of Anisoptera are wings derived from adult animals, one specimen is the adult Zygoptera: Sieblosiidae described herein, and the rest represent nymphal stages or exuviae thereof attributable to various odonate families (Wedmann, 2000;Wedmann et al, 2010;Brockhaus et al, 2020). One of these wings is attributable to the family Macromiidae (Brockhaus et al, 2020), and another one is too incomplete to allow further conclusions.…”
Section: Introductionmentioning
confidence: 95%
“…; Wedmann et al . ) and colour patterning in fossil molluscs (Hagdorn and Sandy ), insects (Fig. ; Wang et al .…”
Section: Institutional Abbreviationsmentioning
confidence: 99%